Variable routes to genomic and host adaptation among coronaviruses. (10th March 2021) - Montoya, Vincent; McLaughlin, Angela; Mordecai, Gideon J.; Miller, Rachel L.; Joy, Jeffrey B.
Abstract: Natural selection operating on the genomes of viral pathogens in different host species strongly contributes to adaptation facilitating host colonization. Here, we analyse, quantify and compare viral adaptation in genomic sequence data derived from seven zoonotic events in the Coronaviridae family among primary, intermediate and human hosts. Rates of nonsynonymous ( d N ) and synonymous ( d S ) changes on specific amino acid positions were quantified for each open reading frame (ORF). Purifying selection accounted for 77% of all sites under selection. Diversifying selection was most frequently observed in viruses infecting the primary hosts of each virus and predominantly occurred in the orf1ab genomic region. Within all four intermediate hosts, diversifying selection on the spike gene was observed either solitarily or in combination with orf1ab and other genes. Consistent with previous evidence, pervasive diversifying selection on coronavirus spike genes corroborates the role this protein plays in host cellular entry, adaptation to new hosts and evasion of host cellular immune responses. Structural modelling of spike proteins identified a significantly higher proportion of sites for SARS‐CoV‐2 under positive selection in close proximity to sites of glycosylation relative to the other coronaviruses. Among human coronaviruses, there was a significant inverse correlation between the number of sites under positive selection and the estimated years since the virus was introduced into the human population. Abundant diversifying selection observed in SARS‐CoV‐2 suggests the virus remains in the adaptive phase of the host switch, typical of recent host switches. A mechanistic understanding of where, when and how genomic adaptation occurs in coronaviruses following a host shift is crucial for vaccine design, public health responses and predicting future pandemics. Abstract : Colonization of a novel host by a virus is typically followed by substantial genomic adaptation for processes involved with host cellular entry, viral replication, and evasion from the host immune system. Here, we use a whole genome sequencing approach to analyze viral genomic adaptation for all known hosts of the 7 coronaviruses which have zoonotically jumped into humans. We show that selection most often occurs in primary hosts, and on replication, host‐ cellular entry, and immune evasion genes. Modeling of spike proteins revealed selected sites of SARS‐CoV‐2 close to glycan attachment sites more often than in other coronaviruses.